Post-revitalization of traditional market in a marketing perspective - Lenti Susanna Saragih; Selviana Vony Meak (Universitas Pendidikan Nasional, 2021)
Revitalizing traditional markets is one of the government's efforts to reform the traditional market conditions both physically and non-physically. Badung Traditional Market is one of the revitalized markets based on the Republic of Indonesia's Minister of Trade Regulation No.37 / M-DAG / 5/2017 concerning guidelines for the development and management of trade facilities. This research aimed to determine the perceptions of traders and consumers after the revitalization of the Badung Market and the role of the Regional Company (PD) in market management after the revitalization of Badung Market. The research was conducted at Denpasar City Badung Market. It was conducted in qualitative research design. Traders, consumers, and markets were chosen to be research informants. The results of this research stated that after the revitalization of Badung Market, it experienced a significant change. Traders’ and consumers' perceptions respond positively to the physical and non-physical changes in Badung Market. The Badung Market physically becomes better with modern buildings according to local wisdom while the non-physically, market educates traders to be more friendly, smarter and market school facilities for the children of transport service workers. The revitalization of the Badung market had an impact on increasing the turnover of vegetable traders on the 2nd floor, especially in the back, but has not increased.